2018
DOI: 10.1071/an16721
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional parameters of beef heifers fed diets with different roughages

Abstract: The purpose of this study was to evaluate intake, digestibility and efficiency of microbial protein synthesis of beef heifers fed with sugarcane silage with different calcium oxide (CaO) levels (0, 7.5; 15 g/kg), fresh sugarcane and corn silage. The same concentrate was offered at 5 g/kg bodyweight (BW) for every diet. Five ruminally and abomasally fistulated beef heifers (373.8 ± 33.12 kg BW) were used in a 5 × 5 Latin square design. Heifers fed sugarcane silage diets presented lower dry matter (DM) intake th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…It is possible that the observed increase in the intake of NFC—with the increases in the intake of NDF—has provided a linear increase in the intake of TDN in sheep. Moraes et al (2018) also observed increases in the intake of TDN for cattle when the sugarcane silage was added.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…It is possible that the observed increase in the intake of NFC—with the increases in the intake of NDF—has provided a linear increase in the intake of TDN in sheep. Moraes et al (2018) also observed increases in the intake of TDN for cattle when the sugarcane silage was added.…”
Section: Discussionmentioning
confidence: 92%
“…It is possible that the observed increase in the intake of NFC-with the increases in the intake of NDF-has provided a linear increase in the intake of TDN in sheep. Moraes et al (2018) et al, 2015) favoring the access and adherence of microruminal organisms to the potentially digestible fraction of NDF (Donnelly et al, 2018). In addition, the improvement in the silage fermentation pattern provided by the inclusion of DCBM may have increased the levels of soluble NDF (pectic substances) in the residual NDF of the silage (Wang et al, 2020), which may also contribute to the increase in digestibility of NDF in the diet.…”
Section: Discussionmentioning
confidence: 99%